Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa (FASA) Annual Workshop Report - Yossa, Rodrigue (WorldFish, 2023)
The purpose of the 2022 Annual workshop of the project “Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa (FASA)” was to bring together project partners to meet in person, discuss the overall project goal and the specific project activities in each country, and conduct the 2023 annual planning for the FASA project.